Термодинамический расчет диаграммы плавкости системы B–B₂O₃–BN при 5 ГПа - Туркевич, В.З.; Прихна, Т.О.; Туркевич, Д.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The melting diagram of the B–B₂O₃–BN ternary system at 5 GPa has been calculated in the framework of phenomenological thermodynamics models. The literature data has been used for the model stability parameters and the unknown interaction parameters of models have been defined from the experimental studies of the phase equilibria. The diagram is characterized by the existence of two eutectic, one peritectic and the maximum in univariant eutectic line invariant equilibria.